Recruitment Status of Coral Reefs (Scleractinian) after Earthquake and Tsunami in North Pagai Island of Mentawai Islands Regency - Suparno Pranoto; Arlius Arlius (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Recruitment of coral is marked by the appearance of reef colonies that are still juvenile. Coral recruitment data after the earthquake and tsunami are very few either in Indonesia or in other part of the world. The purpose of this study is to analyze the level of recruitment and to analyze recruitment diversity of coral reef Scleractinian in the waters affected by tsunami (west coast) and not affected by tsunami (east coast) of North Pagai Island. The observation on coral recruitment used benthic quadrate sampling method with a size of 1x1m2 and the diameter of colony taken measured between 0.5–10 cm. The result of the study shows that the average of recruitment density at the west coast (affected by tsunami) ranged between 0.78–3.67 colonies.m-2 and at the east coast (not affected by tsunami) ranged between 5.11–11.67 colonies.m-2. Coral recruitment level of the east coast is within the category of medium to very high while coral recruitment level of the west coast is in very low to low category. Diversity index (H') of east coast and west coast ranged between 1.55–2.54 with medium category, evenness index (E) of east coast and west coast ranged between 0.87–0.97 with stable category, and dominance index (C) with values ranging from 0.10–0.13 with low category.. Types of coral Porites cylindrica is growing rapidly and has the highest level of recruitment after the tsunami. Keywords: recruitment reef, tsunami, coral, North Pagai Island